EVALUASI PORTOFOLIO BERDASARKAN RISK TOLERANCE PADA BAPAK SUGIHARTO - , Arie Yudhistira ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This thesis is a research on the client named Mr. Sugiharto (name suppressed), which includes HNWIs (High Net Worth Individuals). The goal of this thesis to evaluate the client's portfolio by identifying risk tolerance and problems that exist in client portfolios, and then managing clientâs portfolio by recommending a portfolio of investment instruments on a client by paying attention and adjusting risk tolerance or risk tolerance of clients and the risk of investment instruments are recommended. The author of this thesis has done this research by collecting client's personal financial statement data through interviews and clientâs risk tolerance questionnaire. The data gathered was used to analyze and identify problems in client portfolios. Finally the author recommend the investment instruments and portfolios that best suited the client's risk tolerance. Client portfolios management done by the author resulting in increased clientâs total net worth and the amount of cash flow after the author recommend the two scenarios. The difference between these two scenarios are the amount of the allocation of funds and investment instruments recommended.